Integrated starter-generator using switched reluctance electric motor for N1 category vehicles - Feofanov, S. A.; Feofanova, L. S. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
Demands to reduce exhaust gas emissions are increasing in proportion to the growth trends in the number of vehicles on the planet. Hybrid and electric vehicles solve the problem, but they are quite expensive and require additional charging infrastructure, the rapid development of which is impossible in some countries. Reducing emissions can be achieved through the use of additional electrical devices and an integrated 48V starter generator (ISG) with start-stop, boost and recuperation functions. The article discusses the practical experience of research on ISG based on a switched reluctance electrical machine (SRM). The results of research on N1vehicles with ISG. Test results of reducing fuel consumption and exhaust fumes emission are presented. The efficiency value of motor and generator operating modes of SRM is showed. The hybrid energy source with ultracapacitors showed reliable starting of the internal combustion engine at a temperature of −35 C. The issues of changing vibration characteristics, control strategy and improvement of control algorithms are considered. Results of efficiency increase in the range of rotation frequencies up to 2500 rpm are presented